The Use of Powtoon as Media to Enhance EFL Students’ English Skill - Putu Yuliantini (Journal of Educational Study, 2021)
The title of this research was “The Use of Powtoon as Media to Enhance EFL students’ English Skill”. This study aims to explain that the use of Powtoon as media could enhance EFL students' English skill such as listening, speaking, reading, writing and the benefit of Powtoon as learning media. Technology was growing fast. However, the teacher was still could not adapt to technology in the teaching and learning process. Therefore, the lack of good learning media makes students found some difficulties in understanding the material. The research design used the library research method that collected data from some articles, journals, books, and library resources. Based on the findings, Powtoon could be a solution to enhance EFL students' English skills to have good communication skill in the learning process. Powtoon has many beneficial features such text, music, animation, characters, and audio-visual for EFL students in enhancing their English skills, such as listening, speaking, reading, and writing.